Analisis Beban Kerja Mental dengan National Aeronautics and Space Administration - Task Load Index - Umi Nadhirah (EDUPEDIA Publisher, 2023)
Objective: This study aims to analyze the mental workload felt by the Principal of the Center for Community Learning Activities (PKBM) in the South Jakarta area using the National Aeronautics and Space Administration - Task Load Index (NASA - TLX) method. Methods: This study used a descriptive method with a quantitative approach by calculating mental workload using the NASA-TLX questionnaire. The research was conducted from July 2020 to March 2021. Results: The result of this research showed that 16% of respondents had a very high workload during the Covid-19 pandemic, while 81% of respondents were in the high category, and 3% were in the normal category. Conclusion: Based on this assessment, strategic steps are needed to reduce the workload each PKBM Principal feels, especially those in the High and Very High categories.